2019
DOI: 10.1016/j.brainres.2019.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem correlates of concurrent speech identification in adverse listening conditions

Abstract: When two voices compete, listeners can segregate and identify concurrent speech sounds using pitch (fundamental frequency, F0) and timbre (harmonic) cues. Speech perception is also hindered by the signal-to-noise ratio (SNR). How clear and degraded concurrent speech sounds are represented at early, pre-attentive stages of the auditory system is not well understood. To this end, we measured scalp-recorded frequency-following responses (FFR) from the EEG while human listeners heard two concurrently presented, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 122 publications
(220 reference statements)
2
10
0
Order By: Relevance
“…The changes in F0 amplitudes and the shifts in the latency of V peak did not predict accuracy among monolingual listeners. These results align with those of Yellamsetty and Bidelman [ 98 ], who showed that F0 amplitudes failed to predict the accuracy of listeners’ identification, but contradict with others (e.g., [ 34 , 76 , 128 ]) who found a relationship between subcortical neural processing and perceptual performance in noise among monolingual speakers. We suggest that the main reason for not finding a significant perceptual-neural correlation among monolinguals in the current study is that noise deteriorated their perception to a lesser extent compared to bilinguals.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The changes in F0 amplitudes and the shifts in the latency of V peak did not predict accuracy among monolingual listeners. These results align with those of Yellamsetty and Bidelman [ 98 ], who showed that F0 amplitudes failed to predict the accuracy of listeners’ identification, but contradict with others (e.g., [ 34 , 76 , 128 ]) who found a relationship between subcortical neural processing and perceptual performance in noise among monolingual speakers. We suggest that the main reason for not finding a significant perceptual-neural correlation among monolinguals in the current study is that noise deteriorated their perception to a lesser extent compared to bilinguals.…”
Section: Discussionsupporting
confidence: 86%
“…From the physiological aspect, the responses elicited in noise were diminished and degraded, consistent with previous findings [ 30 , 47 , 76 , 77 , 97 99 ]. This reduction can reflect neural desynchronization [ 98 , 100 ] and less efficient efferent processing [ 20 ]. Neural group differences were reflected in noise, where earlier neural latencies were observed in bilinguals compared to their monolingual peers.…”
Section: Discussionmentioning
confidence: 99%
“…The FFR provides insight into the peripheral representation of speech and is a useful tool for investigating temporal processing deficits (Basu et al, 2010;Hornickel et al, 2012;Kraus et al, 2017). In addition, the FFR may be used to investigate the robustness of speech representations in noise or a dual stream paradigm (Yellamsetty and Bidelman, 2019). The FFR is believed to detect the integrated activity of several nonlinear processing stages along the auditory pathway, and hence various nonlinear features of the stimulus can contribute to the FFR (Lerud et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Intellectual factors also influence the readiness of children to learn English (Giroud et al, 2020). Intellectual factors can also affect how children learn a language (Grogan et al, 2012;Yellamsetty & Bidelman, 2019). Children who have an average IQ need more time to understand the contents of the reading compared to children with a high IQ (Bonifacci & Tobia, 2016).…”
Section: Internal Factorsmentioning
confidence: 99%